Bilateral acute myopia and angle-closure glaucoma in a migraine patient receiving Topiramate: a case report - Gokce, Sabite Emine; Kutluk, Sedef; Yarangumeli, Alper; Kural, Gulcan (The European Research Journal, 2016)
We present a case of topiramate-induced angle-closure glaucoma that was treated with cycloplegia. A 40-year-old woman with a history of migraine presented with bilateral acute onset of blurred vision and headache. She had been prescribed 50 mg of oral topiramate bid for migraine prophylaxis 10 days prior to her presentation. On her ocular examination visual acuity was 20/20 with a myopic correction of -4.0 diopters in both eyes. Bio-microscopic examination revealed bilateral shallow peripheral anterior chambers. Intraocular pressures were 37 OD and 36 OS. On gonioscopic examination bilateral 360 degrees of angle closure was seen. B-scan ultrasonography showed peripheral choroidal effusions. The mainstay of the treatment for topiramate induced secondary angle closure is cyloplegia. Whenever a case of bilateral acute angle-closure glaucoma associated with myopia and shallow anterior chambers is encountered, ciliochoroidal effusion syndrome induced by drugs should be considered in the differential diagnosis.